Antioxidant Efficiency of Irganox® 1010 on Processing and Properties of Plasticized Poly(3-Hydroxybutyrate) Films - Quispe, Mayte M.; López, Olivia V.; Villar, Marcelo A. (Journal of Composites and Biodegradable Polymers, 2021)
Polyhydroxybutyrate (PHB) is one of the few biopolymers that can be processed at industrial scale. Nevertheless, PHB applications in film form are limited, mainly due to the high biopolymer crystallinity and its narrow thermal processing window. In this work, it was studied the effect of glycerol tributyrate (GTB) incorporation as plasticizer, in addition to Irganox® 1010 (I) as phenolic antioxidant on the processability and final properties of PHB-based films. PHB was melt processed in the presence of GTB (5-30 %w/w, PHB basis) and Irganox® (0.3 %w/w, PHB basis) and films were obtained by thermo-compression. PHB films without the plasticizer and the antioxidant were used as control sample. Thermal properties of films demonstrated that PHB thermal processing window was increased due to a synergistic effect of both additives. Improvement can be attributed to changes in the crystalline structure corroborated by X-ray Diffraction (XRD) and Differential Scanning Calorimetry (DSC). Oxygen Transmission Rate (OTR) of PHB films increased in the presence of GTB and Irganox due to the crystalline changes induced by both additives.